Small scatter and nearly isothermal mass profiles to four half-light radii from two-dimensional stellar dynamics of early-type galaxies - Cappellari, M; Romanowsky, A; Brodie, J; Forbes, D; Strader, J; Foster, C; Kartha, S; Pastorello, N; Pota, V; Spitler, L; Usher, C; Arnold, J (American Astronomical Society, 2015)
We study the total mass-density profile for a sample of 14 fast-rotator early-type galaxies (stellar masses ). We combine observations from the SLUGGS and ATLAS surveys to map out the stellar kinematics in two dimensions, out to a median radius for the sample of four half-light radii Re (or 10 kpc) and a maximum radius of 2.0-6.2 Re (or 4-21 kpc). We use axisymmetric dynamical models based on the Jeans equations, which allow for a spatially varying anisotropy; employ quite general profiles for the dark halos; and, in particular, do not place any restrictions on the profile slope. This is made possible by the availability of spatially extended two-dimensional kinematics. We find that our relatively simple models provide a remarkably good description of the observed kinematics. The resulting total density profiles are well described by a nearly isothermal power law from Re/10 to at least 4Re, the largest average deviation being 11%. The average logarithmic slope is with observed rms scatter of just . This scatter out to large radii, where dark matter dominates, is as small as previously reported by lensing studies around r ≈ Re/2, where the stars dominate. Our bulge-halo conspiracy places much tighter constraints on galaxy formation models. It illustrates the power of two-dimensional stellar kinematics observations at large radii. It is now important to test the generality of our results for different galaxy types and larger samples.